2016
DOI: 10.1128/mcb.00230-16
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of the 3-Phosphoinositide-Dependent Protein Kinase 1 (PDK1) Substrate-Docking Site in the Developing Brain Causes Microcephaly with Abnormal Brain Morphogenesis Independently of Akt, Leading to Impaired Cognition and Disruptive Behaviors

Abstract: The phosphoinositide (PI) 3-kinase/Akt signaling pathway plays essential roles during neuronal development. 3-Phosphoinositide-dependent protein kinase 1 (PDK1) coordinates the PI 3-kinase signals by activating 23 kinases of the AGC family, including Akt. Phosphorylation of a conserved docking site in the substrate is a requisite for PDK1 to recognize, phosphorylate, and activate most of these kinases, with the exception of Akt. We exploited this differential mechanism of regulation by generating neuron-specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 61 publications
3
20
0
Order By: Relevance
“…However, the density of NeuN+ cells in PDK1 cKO mice was increased as compared to control animals ( Figure 2E ). This finding was in agreement with that reported on PDK1 conditional knock-in mice ( Cordon-Barris et al, 2016 ). Overall, conditional deletion of PDK1 in the forebrain resulted in remarkable loss of mature neurons.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…However, the density of NeuN+ cells in PDK1 cKO mice was increased as compared to control animals ( Figure 2E ). This finding was in agreement with that reported on PDK1 conditional knock-in mice ( Cordon-Barris et al, 2016 ). Overall, conditional deletion of PDK1 in the forebrain resulted in remarkable loss of mature neurons.…”
Section: Resultssupporting
confidence: 94%
“…Recent work showed that conditional deletion of PDK1 through GFAP-Cre mediated gene recombination causes microcephaly in mice, indicating a critical role of PDK1 in brain development ( Chalhoub et al, 2009 ). A conditional knock-in mouse model expressing the PDK1 L155E mutation displays microcephaly as well ( Cordon-Barris et al, 2016 ). In addition, it has been demonstrated that PDK1 in neural progenitor cells (NPCs) is important for the generation of oligodendrocyte precursor cells ( Watatani et al, 2012 ) and neuronal migration ( Itoh et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The Pdk1 L155E genetic model that uncouples AKT-dependent and AKT-independent pathways downstream of PI3K has been previously utilized to show that PI3K-dependent, AKT-independent pathways are required for T cell progenitors proliferation (27), leucine-induced mTORC1/S6K activation in the cardiac muscle (28), and proper brain patterning (29). Our data further extend these concepts by providing clear genetic evidence that activation of AGC kinases controlled by PDK1 via its PIF pocket is critical not only for the proliferative response to PI3K activation, but also for the ability of PI3K to drive neoplastic transformation and tumor progression in three well-characterized mouse models of follicular, poorly differentiated, and anaplastic thyroid cancer, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…As an upstream gene of AKT, PDK1 regulates the activities of AKT and other downstream kinases of PI3K/ AKT, which enables PDK1 to regulate a series of biological responses in cells by the PI3K/AKT signaling pathway (27). PDK1 is a serine/threonine kinase of the AGC protein kinase family.…”
Section: Discussionmentioning
confidence: 99%